2000
DOI: 10.1054/bjoc.2000.1304
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus vinorelbine in elderly or unfit patients with non-small cell lung cancer

Abstract: Summary Cisplatin-based combinations are efficacious in increasing the overall survival of patients with non-small cell lung cancer (NSCLC), but their toxicity makes them unsuitable for elderly and unfit patients. The primary objective of this non-randomized phase II study was to evaluate the feasibility and activity of the gemcitabine plus vinorelbine combination in previously untreated elderly and/or unfit patients with measurable stage III or IV NSCLC. Forty-three patients aged ≥ 65 years or with contraindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 15 publications
2
22
1
Order By: Relevance
“…In phase II trials of vinorelbine plus gemcitabine, response rates were between 18 and 35%, with a median survival time from 10 to 11 months. The regimens were generally well tolerated by elderly patients with advanced NSCLC [11, 12, 21]. Phase II studies on a combination of new cytotoxic agents with cisplatin in modified schedules or attenuated doses also revealed good activity and tolerability [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…In phase II trials of vinorelbine plus gemcitabine, response rates were between 18 and 35%, with a median survival time from 10 to 11 months. The regimens were generally well tolerated by elderly patients with advanced NSCLC [11, 12, 21]. Phase II studies on a combination of new cytotoxic agents with cisplatin in modified schedules or attenuated doses also revealed good activity and tolerability [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a GEM/VNR combination was very well tolerated with high activity (Feliu et al, 1999;Isokangas et al, 1999;Bajetta et al, 2000;Beretta et al, 2000;Gridelli et al, 2000). The Spanish Lung Cancer Group (Alberola et al, 2001) reported on a randomised comparison of a CDDP-based three-drug combination (CDDP/ GEM/VNR) vs non-CDDP sequential doublets (GEM/VNR followed by ifosphamide/VNR) vs CDDP/GEM (reference regimen).…”
Section: Discussionmentioning
confidence: 99%
“…Among the new drugs, GEM/VNR combination is noteworthy because of their demonstrated activity and particularly their good toxicity profile. This combination can also be used for elderly or unfit patients, because of its low toxicities (Feliu et al, 1999;Isokangas et al, 1999;Bajetta et al, 2000;Beretta et al, 2000;Gridelli et al, 2000). In addition, it has been shown that a single treatment of docetaxel (DOC) is active for NSCLC, especially as a second-line treatment (Fossella et al, 2000;Shephard et al, 2000).…”
mentioning
confidence: 99%
“…Phase II studies using gemcitabine and vinorelbine, either as single agents or in combination, have shown activity and a favorable toxicity profile in patients aged 70 years or older, with response rates ranging from 18.4 to 34.9% [19, 20, 21, 22, 23, 24, 25]. …”
Section: Discussionmentioning
confidence: 99%